Commodity risk assessment of ash logs from the US treated with sulfuryl fluoride to prevent the entry of the emerald ash borer Agrilus planipennis. (24th February 2023) - ; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The European Commission submitted to the EFSA Panel on Plant Health a dossier by USDA proposing to use sulfuryl fluoride on ash log shipments to treat Agrilus planipennis for phytosanitary certification. After collecting additional evidence from USDA APHIS, external experts and literature, the Panel performed a quantitative assessment on the likelihood of pest freedom from A. planipennis, at the point of entry in the EU, of two different commodities fumigated with sulfuryl fluoride: (a) ash logs with bark; and (b) debarked ash logs. An expert judgement is given on the likelihood of pest freedom taking into consideration the measures acting on the pest, including uncertainties associated with the assessment. The likelihood of pest freedom from A. planipennis is lower for ash logs with bark compared with debarked ash logs. With 95% certainty, the Panel concludes that between 9, 740 and 10, 000 containers of ash logs with bark per 10, 000 and between 9, 989 and 10, 000 containers of debarked ash logs per 10, 000 will be free from A. planipennis, when fumigated with sulfuryl fluoride at the specific treatment regime proposed by the USDA APHIS.